Geometric features of tumbling mill flows: A positron emission particle tracking investigation. (12th October 2019) - de Klerk, D.N.; Govender, I.; Mainza, A.N.
Highlights: High quality PEPT measurements. Accurate resolution of volume and time averaged Lagrangian trajectory fields. New schemes for equilibrium surface, free surface and centre of circulation. Detailed quantification of the flow geometry with parametric study. Abstract: Positron emission particle tracking (PEPT) allows for the in situ tracking of particles (rocks, balls, slurry) in experimental tumbling mills. For sufficiently long tracking times, the trajectory fields can be cast into time averages per unit volume of kinematic and dynamical information which constitute the key ingredients for fundamental modelling of tumbling mills. Central to this objective is the accurate delineation of geometric features making up the tumbling mill in the azimuthal plane. To this end, algorithms for extracting bulk features of the media (free surface, equilibrium surface, centre of circulation, toe and shoulder positions) are presented. These algorithms are then employed to compare results from dry, batch experiments spanning a wide range of mill speeds, lifter heights and lifter angles.